A novel technique for selective NF-κB inhibition in Kupffer cells: contrary effects in fulminant hepatitis and ischaemia–reperfusion. Issue 12 (25th May 2009) - Hoffmann, F; Sass, G; Zillies, J; Zahler, S; Tiegs, G; Hartkorn, A; Fuchs, S; Wagner, J; Winter, G; Coester, C; Gerbes, A L; Vollmar, A M
Abstract : Background and aims: The transcription factor nuclear factor kappa B (NF-κB) has risen as a promising target for anti-inflammatory therapeutics. In the liver, however, NF-κB inhibition mediates both damaging and protective effects. The outcome is deemed to depend on the liver cell type addressed. Recent gene knock-out studies focused on the role of NF-κB in hepatocytes, whereas the role of NF-κB in Kupffer cells has not yet been investigated in vivo. Here we present a novel approach, which may be suitable for clinical application, to selectively target NF-κB in Kupffer cells and analyse the effects in experimental models of liver injury. Methods: NF-κB inhibiting decoy oligodeoxynucleotides were loaded upon gelatin nanoparticles (D-NPs) and their in vivo distribution was determined by confocal microscopy. Liver damage, NF-κB activity, cytokine levels and apoptotic protein expression were evaluated after lipopolysaccharide (LPS), d -galactosamine (GalN)/LPS, or concanavalin A (ConA) challenge and partial warm ischaemia and subsequent reperfusion, respectively. Results: D-NPs were selectively taken up by Kupffer cells and inhibited NF-κB activation. Inhibition of NF-κB in Kupffer cells improved survival and reduced liver injury after GalN/LPS as well as after ConA challenge. While anti-apoptotic protein expression in liver tissue was not reduced, pro-apoptotic players such as cJun N-terminal kinase (JNK) were inhibited. In contrast, selective inhibition of NF-κB augmented reperfusion injury. Conclusions: NF-κB inhibiting decoy oligodeoxynucleotide-loaded gelatin nanoparticles is a novel tool to selectively inhibit NF-κB activation in Kupffer cells in vivo. Thus, liver injury can be reduced in experimental fulminant hepatitis, but increased at ischaemia–reperfusion.